Impact of the Time Proportion of Respiratory Phases on Dosimetry in SBRT of Lung Tumor Near the Chest Wall or Diaphragm. (26th September 2019) - Sun, Xuanzi; Li, Yi; Li, Junjun; Zhang, Xiaozhi
Purpose: Large tumor motion often leads to larger dosimetric variation, especially in lung tumors located in lower lobe and adhered to chest wall or diaphragm. The purpose of this work is to discuss the impact of the time proportion of each respiratory phase on dosimetry in stereotactic body radiation therapy with lung cancer tumor close to chest wall or diaphragm. Methods: Participants include 14 patients with lung cancer located in the lower lobe. Each patient received treatment planning 3-dimensional computed tomography and an additional 4-dimensional computed tomography simulation under free-breathing condition. The percentage of time intervals for each respiratory phase in a whole respiratory cycle was calculated from respiratory motion curves recorded during 4-dimensional computed tomography scanning. Treatment plan was made upon treatment planning 3-dimensional computed tomography and then transformed onto each image of 4-dimensional computed tomography. The transformed doses on each image of 4-dimensional computed tomography were accumulated with equal weight or with weight of time proportion for each respiratory phase. Results: Compared to treatment planning 3-dimensional computed tomography dose, the mean dose of tumor, affected lung, contralateral lung, bilateral lungs, and V20 of affected lung decreased by 2.7%, 4.5%, 1.5%, 1.2%, and 4.1%, respectively, after equal-weighted accumulation, while mean dose of heart increased by 3.6% ( P < .05). Accumulated dose with weight of actual time proportion decreased in the mean dose of tumor, affected lung, contralateral lung, bilateral lungs, and V20 of affected lung by 2.37%, 5.19%, 3.61%, 3.46%, and 5.08%, respectively compared to treatment planning 3-dimensional computed tomography dose, but mean dose of heart increased by 5.12% ( P < .05). Conclusions: Doses received by tumor, lungs, and heart changed more significantly after time-weighted 4-dimensional accumulation than equal-weight 4-dimensional accumulation. Utilizing 4-dimensional computed tomography and deformable image registration to introduce time proportions of each respiratory phase to dose distribution evaluation is of significance for accuracy in lung cancer during stereotactic body radiation therapy treatment.